Efektivitas Pertimbangan Hakim dalam Menjatuhkan Putusan atas Perkara Kekerasan dalam Lingkup Kekeluargaan (Studi Kasus di Pengadilan Negeri Lubuk Pakam) - Raja Songkup Pratama; Parlaungan Gabriel Siahaan; Dewi Pika Lumban Batu; Yuli Indriani Lubis; Pebryna Riosa Siburian; Rahmi Siregar (QISTINA: Jurnal Multidisiplin Indonesia, 2025)
This study aims to analyze the effectiveness of judges’ considerations in delivering verdicts in cases of domestic violence, using a case study of decision number 1076/Pid.B/2025/PN Lbp at the Lubuk Pakam District Court. This research employs a qualitative descriptive method with a case study approach through direct courtroom observation, documentation, and literature review. The findings reveal that the judge’s considerations encompassed juridical, sociological, and psychological aspects in a balanced manner. The judgment was based not only on legal evidence but also on the social context of the family relationship between the defendant and the victim. The four-month imprisonment sentence demonstrates an attempt to balance legal certainty, substantive justice, and humanity. This study emphasizes the importance of judges’ sensitivity to social dimensions in family violence cases so that verdicts serve not only as punitive measures but also as restorative and educational acts of justice.